2004
DOI: 10.3766/jaaa.15.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Success with Hearing Aids in Everyday Living

Abstract: Persons with impaired hearing who are candidates for amplification are not all equally successful with hearing aids in daily living. Having the ability to predict success with amplification in everyday life from measures that can be obtained during an initial evaluation of the patient's candidacy would result in greater patient satisfaction with hearing aids and more efficient use of clinical resources. This study investigated the relationship between various demographic and audiometric measures, and two measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
69
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 20 publications
12
69
3
2
Order By: Relevance
“…Killion and Gudmundsen (2005) did an evidenced-based review on the correlation between prefitting measures and hearing aid satisfaction based on self-report measures. In none of the reviewed studies significant correlations were found between traditional unaided prefitting speech measures and hearing aid satisfaction, except in a study by Walden and Walden (2004) for speech perception in noise. Wesselkamp, Margolf-Hackl, and Kiessling (2001) and Pastoors, Gebhart, and Kiessling (2001) investigated the effect of a fitting strategy based on loudness scaling.…”
Section: Introductionmentioning
confidence: 99%
“…Killion and Gudmundsen (2005) did an evidenced-based review on the correlation between prefitting measures and hearing aid satisfaction based on self-report measures. In none of the reviewed studies significant correlations were found between traditional unaided prefitting speech measures and hearing aid satisfaction, except in a study by Walden and Walden (2004) for speech perception in noise. Wesselkamp, Margolf-Hackl, and Kiessling (2001) and Pastoors, Gebhart, and Kiessling (2001) investigated the effect of a fitting strategy based on loudness scaling.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with mild to moderate sensorineural hearing loss (SNHL) have significantly higher sentence reception thresholds (SeRTs), even with hearing aids [2][3][4][5], than subjects with normal hearing. This finding reflects a degradation of the acoustic cues that have their greatest impact on consonant discrimination [6].…”
Section: Introductionmentioning
confidence: 99%
“…For severe hearing losses, the potential HA performance is limited by an insufficient residual dynamic range [Zwartenkot et al, 2014] and the aversiveness to the high levels of acoustic amplification . Additionally, the effect of aging on cognitive processes is a major contributing factor affecting HA performance [Walden and Walden, 2004;Müller et al, 2016].…”
Section: Introductionmentioning
confidence: 99%